2019
DOI: 10.1108/ec-08-2018-0378
|View full text |Cite
|
Sign up to set email alerts
|

Application of biharmonic equation in impeller profile optimization design of an aero-centrifugal pump

Abstract: Purpose The purpose of this paper is to improve the hydraulic efficiency without changing the overall dimension. The blade profile optimization design of the aero-centrifugal pump based on the biharmonic equation surrogate model has been studied. Design/methodology/approach First of all, Bezier curves and linear function are used to control the annular angle distribution and the stacking angle of blade profile under the MATLAB platform. Grid independence analysis has been studied to find the finest mesh sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Box and Wilson presented the Reaction Surface Methodology (RSM) in 1951; it is a technique for estimating the combined effect of several independent variables that do not require the performance of factorial design experiments for all of the independent variables at each level. RSM (Liu et al, 2019;Meng et al, 2022)is a technique that can be found in the field of chemical engineering.…”
Section: Methodsmentioning
confidence: 99%
“…Box and Wilson presented the Reaction Surface Methodology (RSM) in 1951; it is a technique for estimating the combined effect of several independent variables that do not require the performance of factorial design experiments for all of the independent variables at each level. RSM (Liu et al, 2019;Meng et al, 2022)is a technique that can be found in the field of chemical engineering.…”
Section: Methodsmentioning
confidence: 99%
“…[10] Impeller high-pressure and low-pressure side diameter, impeller low-pressure side hub diameter, impeller high-pressure side exit width Hydraulic efficiency in differient mass flow rate CFD and Experiment MOGA Wang et al [11] Hub inlet angle, hub exit angle, hub wrap angle, leading-edge wrap angle at hub, shroud inlet angle, shroud exit angle, shroud wrap angle, and the leading edge wrap angle at the shroud Efficiency and NPSHr CFD and Experiment MOGA Derakhshan et al [7] Hub diameter, suction diameter, impeller diameter, impeller width, inlet, and outlet blade angles Efficiency and total pressure difference CFD and Experiment ABC Derakhshan and M. Bashiri. [12] Hub diameter, suction diameter, impeller diameter, impeller width, and inlet and outlet blade angles Efficiency and total pressure difference CFD and Experiment ES Liu et al [13] Hub streamline and shroud streamline Hydraulic efficiency CFD and Experiment AFSA Wang et al [14] Four angles for the sweep and lean Efficiencies at two working points and total pressure ratio CFD NSGA-II Zhao et al [5] Blade outlet angle, blade inlet angle, splitter offset angle, impeller meridional section Anti-cavitation ability and the hydraulic efficiency CFD and Experiment NSGA-II Pei et al [15] The shroud radius, the hub radius, the shroud angle, and the hub angle As can be seen in Table 1, a problem that existed in the past research is that major parameters affecting the performance of LSSCP, namely head, efficiency, shaft power, and suction capability, have not been fully considered as the optimization objectives. This is due to the shortcomings of the global optimization algorithm, such as encoding complexity and long iterations.…”
Section: Reference Design Variables Optimization Objectives Methods Optimization Algorithmmentioning
confidence: 99%
“…It is preferred in the design of pumps in previous research because of its advantage in reaching the global optimum. Table 1 summarizes the global optimization method used for the performance optimization of pumps commonly in recent years, including multi-objective genetic algorithm (MOGA) [9][10][11], artificial bee colony (ABC) [7], eagle strategy (ES) [12], artificial fish swarm algorithm (AFSA) [13], and non-dominated sorting genetic algorithm-II (NSGA-II) [14][15][16][17]. Pei et al used the particle swarm optimization algorithm to arrange the optimal solution of the impeller parameters and efficiency of LSSCP, and performance of LSSCP was improved after optimization [3].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the table that the outlet diameter of the optimized centrifugal pump impeller is significantly reduced, and the number of blades is reduced. This is beneficial to reduce the friction loss of centrifugal pump impeller disk, thus reducing the energy loss of centrifugal pump [32][33]. At the same time, the outlet angle of the optimized centrifugal pump blade is obviously reduced.…”
Section: Figure 7 Fitness Value Of Uniform Objective Functionmentioning
confidence: 99%